Transcriptional and metabolomic responses of Methylococcus capsulatus Bath to nitrogen source and temperature downshift - Bedekar, Ashwini Ashok; Deewan, Anshu; Jagtap, Sujit S.; Parker, David A.; Liu, Ping; Mackie, Roderick I.; Rao, Christopher V. (Frontiers in Microbiology, 2023)
Methanotrophs play a significant role in methane oxidation, because they are the only biological methane sink present in nature. The methane monooxygenase enzyme oxidizes methane or ammonia into methanol or hydroxylamine, respectively. While much is known about central carbon metabolism in methanotrophs, far less is known about nitrogen metabolism. In this study, we investigated how Methylococcus capsulatus Bath, a methane-oxidizing bacterium, responds to nitrogen source and temperature. Batch culture experiments were conducted using nitrate or ammonium as nitrogen sources anaerobic at both 37 °C and 42 °C. While growth rates with nitrate and ammonium were comparable at 42 °C, a significant growth advantage was observed with ammonium at 37 °C. Utilization of nitrate was higher at 42 °C than at 37 °C, especially in the first 24 hours. Use of ammonium remained constant between 42 °C and 37 °C; however, nitrite buildup and conversion to ammonia were found to be temperature-dependent processes. We performed RNA-seq to understand the underlying molecular mechanisms, and the results revealed complex transcriptional changes in response to varying conditions. Different gene expression patterns connected to respiration, nitrate and ammonia metabolism, methane oxidation, and amino acid biosynthesis were identified using gene ontology analysis. Notably, key pathways with variable expression profiles included oxidative phosphorylation and methane and methanol oxidation. Additionally, there were transcription levels that varied for genes related to nitrogen metabolism, particularly for ammonia oxidation, nitrate reduction, and transporters. Quantitative PCR was used to validate these transcriptional changes. Analyses of intracellular metabolites revealed changes in fatty acids, amino acids, central carbon intermediates, and nitrogen bases in response to various nitrogen sources and temperatures. Overall, our results offer improved understanding of the intricate interactions between nitrogen availability, temperature, and gene expression in M. capsulatus Bath. This study enhances our understanding of microbial adaptation strategies, offering potential applications in biotechnological and environmental contexts.